The Al Wahbah Crater of Saudi Arabia and its geotourism potential - Kaminski, Michael; Garrison, Thomas (Geotourism/Geoturystyka, 2025)
The Al Wahbah Crater of Harrat Kishb in western Saudi Arabia is an impressive (2 km wide, 250 m deep) maar crater that formed explosively when rising magma encountered an aquifer during Pleistocene times. The crater and surrounding areas display several Quaternary and Recent volcanic features that are of interest to geoscientists, including a volcanoclastic ejecta layer, an elevated crater rim, scoria fields, an oasis with a natural mineral spring, an ephemeral playa lake on the crater floor, and a pre-existing volcano that was bisected by the explosion. The ejecta layer is overlain by a more recent basaltic lava flow that displays a typical pahoehoe surface. The site is an area of outstanding natural beauty, and new infrastructure is currently being developed to accommodate geotourism. The Al Wahbah Crater is a two-hour drive from the international airport in Taif and can be easily accessed via a major east-west highway and paved local roads.